Using Electromagnetism-like algorithm and genetic algorithm to optimize time of task scheduling for dual manipulators - Abed I.A.; Sahari K.S.M.; Koh S.P.; Tiong S.K.; Jagadeesh P. (2023)
A method based on Electromagnetism-Like algorithm (EM) and Genetic Algorithm (GA) is proposed to determine the time-optimal task scheduling for dual robot manipulators. GA is utilized to calculate the near-optimal task scheduling for the two robots. On top of that, the EM is recommended as a suitable alternative to obtain multiple solutions at each task points for both manipulators with less error. During the course of the tour, the dual robots move from point to point with less cycle time, while ensuring that no collision occurs between the two manipulators or between the dual manipulators and the static obstacles in the workspace. The movement and the configurations of the manipulators at the task points were visualized using a simulator developed via Visual Basic. Net. The method is verified using two simulators acting as examples for two identical four-link planar robots working in the environment, with square-shaped obstacles cluttered at different locations. 2013 IEEE.